2.3

From The Algorithm Design Manual Solution Wiki
Revision as of 18:49, 9 September 2020 by Algowikiadmin (talk | contribs) (Created page with "<math>f(n) = (((n^2)(n+1)^2)/8) + n(n+1)(2n+1)/12</math> ---- This problem does appear to break down into a series of nested summations: <math> \displaystyle\sum_{i=1}^{n}\te...")
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search

[math]\displaystyle{ f(n) = (((n^2)(n+1)^2)/8) + n(n+1)(2n+1)/12 }[/math]


This problem does appear to break down into a series of nested summations:

[math]\displaystyle{ \displaystyle\sum_{i=1}^{n}\text{ } \displaystyle\sum_{j=1}^{i}\text{ } \displaystyle\sum_{k=j}^{i+j}\text{ } \displaystyle\sum_{l=1}^{j+i-k}1 }[/math]

In the last summation, the formula is independent of the iterator, which translates into adding the value 1, [math]\displaystyle{ j+i-k }[/math] times:

[math]\displaystyle{ \displaystyle\sum_{i=1}^{n} \displaystyle\sum_{j=1}^{i} \displaystyle\sum_{k=j}^{i+j}(j+i-k) }[/math]

Now the third summation goes from [math]\displaystyle{ j }[/math] to [math]\displaystyle{ i+j }[/math] the formula on closer examination reveals that

[math]\displaystyle{ \displaystyle\sum_{k=j}^{i+j}(j+i-k) }[/math] is [math]\displaystyle{ \displaystyle\sum_{k=1}^{i}(k) }[/math] which is equal to [math]\displaystyle{ i*(i+1)/2 }[/math]

Since [math]\displaystyle{ \displaystyle\sum_{k=start}^{end}(end-k) = \displaystyle\sum_{k=1}^{end-start}(k) }[/math]

So the summation boils down to

[math]\displaystyle{ \displaystyle\sum_{i=1}^{n} \displaystyle\sum_{j=1}^{i} (i*(i+1)/2) }[/math]

The formula in the second summation is independent of the iterator, which translates to adding [math]\displaystyle{ i*(i+1)/2 }[/math], [math]\displaystyle{ i }[/math] times.

[math]\displaystyle{ \displaystyle\sum_{i=1}^{n}(i^2 * (i+1)/2) }[/math]

which is

[math]\displaystyle{ \displaystyle\sum_{i=1}^{n}((i^3 + i^2)/2) }[/math]


[math]\displaystyle{ \frac{1}{2} \left(\Sigma r^3 + \Sigma r^2\right) = \frac{1}{2}\left(\frac{n^2\left(n+1\right)^2}{4} + \frac {n \left(n+1\right)\left(2n+1\right)}{6}\right) = \frac{n^2\left(n+1\right)^2}{8} + \frac {n \left(n+1\right)\left(2n+1\right)}{12} }[/math]


Time Complexity = O[math]\displaystyle{ ({n}^{4}) }[/math]



Back to Chapter 2